Molecular characterization of lactococcal bacteriophage Tuc2009 and identification and analysis of genes encoding lysin, a putative holin, and two structural proteins. - Arendt, E K (1994)
Bacteriophage Tuc2009 is a temperate bacteriophage with a small isometric head and is isolated from Lactococcus lactis subsp. cremoris UC509. The phage genome is packaged by a headful mechanism, giving rise to circularly permuted molecules with terminal redundancy. The unit genome size is approximately 39 kb. A map of the phage genome on which several determinants could be localized was constructed: pac, the site of initiation of DNA packaging; lys (1,287 bp), specifying the phage lysin; S (267 bp), specifying a putative holin; and mp1 (522 bp) and mp2 (498 bp), each specifying one of the phage's structural proteins. lys, S, mp1, and mp2 were further characterized. lys and S are partially overlapping and appear to be part of one operon. The lysin shows homology to the lysins of the Streptococcus pneumoniae phages Cp-9, Cp-1, and Cp-7. The putative holin, which is thought to be involved in the release of lysin from the cytoplasm, contains two strongly hydrophobic presumptive transmembrane domains and a highly charged C-terminal domain.